Prevalence and factors associated with negative emotional state of stress among adult population in Kedah, Malaysia during covid-19 pandemic - Asmail@Ismail, Amalina (2024)
Background: COVID-19 pandemic triggers significant increase in prevalence of stress worldwide. However, the extent and factors associated with psychological distress during COVID-19 in the local population are not adequately explored. Objective: The present study aimed to determine the prevalence and factors associated with negative emotional state of stress among adult population in Kedah, Malaysia during COVID-19 pandemic. Methodology: This is a retrospective record review of adult population aged 18 to 60 years old who were screened for mental health well-being from January 2021 until March 2022 in the state of Kedah. Simple random sampling was applied to obtain the sample size of 562. The participants’ mental health status was assessed using the online platform Depression, Anxiety, Stress Scale-21 (DASS-21). Simple and multiple logistic regression analyses were conducted to determine the factors associated with negative emotional state of stress. Results: The prevalence of negative emotional state of stress was 45.7% (95% CI 41.6%, 49.8%). The majority of them did not have stress (54.3%), followed by severe stress (12.3%), moderate (11.9%), mild (11.7%) and very severe stress (9.8%). The significant factors associated with negative emotional state of stress among adult population in Kedah, Malaysia during COVID-19 pandemic were sex, occupation and Movement Control Order (MCO) period. Female has 3.04 odds more stress compared to male (Adj OR 3.035 95% CI: 2.007 to 4.591, p-value <0.001), being unemployed has 2.17 more odds to experience stress compared to being employed (Adj OR 2.171 95% CI: 1.480 to 3.185, p-value <0.001) and being under MCO were 61.7% less likely to have stress compared to not being under MCO (Adj OR 0.383 95% CI: 0.264 to 0.555, p-value <0.001). Conclusion: The overall prevalence of negative emotional state of stress among adult population during COVID-19 pandemic in Kedah was 45.7%, higher than other studies. Being female and unemployed were associated with stress, while the MCO period was a protective factor against stress. By tailoring interventions and strategies based on the identified characteristics and vulnerabilities of these groups such as cognitive behavioral therapy (CBT) and mindfulness-based interventions, it is possible to implement more targeted and impactful approaches to alleviate negative emotional states of stress.